Peculiarities of organizational changes’ management on freight transport companies - S. A. Borodulina; N. A. Loginova (Вестник СибАДИ)
The authors have developed and justified the basis of the effective management of organizational changes on freight transport companies through detaching projections of three types of factors - labor, economic, production - which take into account the sectoral specificity of functioning enterprises. The received results can be used in developing of corresponding methodological foundations.